THE PECULIARITIES OF PHRASE CONCEPTUALIZATION IN AMERICAN ENGLISH - HUZYNETS, Yulia (Науковий вісник Ужгородського університету. Серія Філологія, 2020)
The article deals with basic peculiarities of phrase conceptualization in American English. The topicality of the article is due to the particular importance of the problems related to the correlation of language, thinking, cognition and culture, the solution of which is based on the principles and methods of cognitive and linguocultural analysis and fundamental views of domestic and foreign researchers. Studying phrases from the standpoint of cognitive approach enables establishing the mechanism of correlation of speech and cognition processes, because it is important to find out how in such specific lin- gual signs, such as phrases, the most varied manifestations of human being are realized.The aim of the study is to identify and analyze the semantic-cognitive features inherent in phraseological units of the American variant of the English language on the basis of knowledge of human and national-specific phenomena of material and spiritual culture, realities and myths of folk life. The object of the work is the verbalization of value concepts with the help of phraseological units in American English. The subject of the study is the structural-semantic features of phraseological units that verbalize value concepts in the above mentioned variant. In the article the subject and tasks of cognitive linguistics are outlined. The most important views of domestic and foreign linguists on the nature of the concept are characterized. The subject of special attention was the importance of the phraseologi- cal unit as part of the semantic content of the concept, as well as its nominative function. The explication of the national identity of the American nation in the phraseological fund of the English language is considered. It was found that phraseological units comrise verbalized cultural codes that reflect the national linguistic model of the world, demonstrating the peculiarities of the national vision of the surrounding reality. Consideration of the phraseological foundation of the American version of the Eng- lish language in the linguistic-cultural aspect made it possible to identify and substantiate the basic values of American culture: self-reliance, hard working, optimism, intelligence, privacy and friendship.